Acceptance, understanding, and the moral imperative of promoting social justice education in the schoolhouse - Young, Nicholas D., 1967-; Jean, Elizabeth, 1963-; Citro, Teresa Allissa (Vernon series in education., 2019)
"This book examines the critical issues associated with the topic of social justice in primary and secondary education. Understanding the challenges related to educational inequity requires a comprehensive and systematic re-examination of educational reform; specifically, this book defines social justice education, offers different perspectives from major thought leaders and examines the challenges faced by different populations when it comes to receiving equal opportunity and treatment. Emphasis will be placed on programs, approaches and strategies to increasingly teach tolerance, respect, and understanding within and between these groups and members of the majority culture. The focus, then, will be on educational practices designed to prepare students from diverse backgrounds to be active, contributing, and fully participatory members of our contemporary society."--Publisher's description